Playing against nature integrating science and economics to mitigate natural hazards in an uncertain world - Stein, Seth (John Wiley & Sons, Inc., 2014)
Defending society against natural hazards is a high-stakes game of chance against nature, involving tough decisions. How should a developing nation allocate its budget between building schools for towns without ones or making existing schools earthquake-resistant? Does it make more sense to build levees to protect against floods, or to prevent development in the areas at risk? Would more lives be saved by making hospitals earthquake-resistant, or using the funds for patient care? What should scientists tell the public when - as occurred in L'Aquila, Italy and Mammoth Lakes, California - there.
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Hazard mitigation; Hazard mitigation -- Economic aspects; Natural disasters -- Economic aspects; Natural disasters -- Risk assessment; Emergency management; Catastrophes; Réduction; Catastrophes; Réduction; Aspect économique; Catastrophes naturelles; Aspect économique; Catastrophes naturelles; Évaluation du risque; BUSINESS & ECONOMICS; Infrastructure; SOCIAL SCIENCE; General; Natural disasters; Economic aspects; Natural disasters; Risk assessment